2016 Good Practice Report : Work Integrated Learning (WIL). - Sachs, Judyth; Rowe, Anna; Wilson, Michael (Dept of Education and Training, Australia, 2016)
The Australian Government Office for Learning and Teaching commissioned this report to identify good practices in work-integrated learning (WIL) in Australia through a systematic review of current approaches in universities in Australia and elsewhere. This report takes up where Janice Orrell's 2011 benchmark report left off and provides contemporary case studies of good practice evident in 13 Australian universities and from two overseas universities. There has been considerable progress since Orrell's report was published, especially around issues of scale, resources, whole of institution approaches, and integration into the curriculum. However, issues around access and equity, Indigenous student participation and international student experience remain works in progress. This report focuses on answering the following questions: What is WIL? What evidence is there that WIL experiences have improved graduate employability? How are WIL programs organised? What are some examples of good practice? What are some of the issues around implementing WIL across a university? For the purposes of this report a good practice is one that has been proven to work well and embodies a successful experience that has been tested and validated in and through practice and from which others, across a variety of contexts, can apply and benefit.